Staffing policies and human resources management in electricity industry in Peninsular Malaysia : the development of Malay engineers, 1949-1990 - Ahmad Kamal Ariffin Mohd Rus; Mohamad Khairul Anuar Mohd Rosli (Penerbit Universiti Kebangsaan Malaysia, 2022)
Towards the second half of twentieth century, the electricity industry in Peninsular Malaysia was gathered in single, nationalized company. The governance structuring strategy to redevelop electricity supply facilities involved every state and the consumer sector that were heavily affected by the Japanese Occupation during World War II causing the need for the expert staff in electrical engineering to be vital. Due to the lack of professional electrical engineers, priority was given to development of human resources involving local staff. This situation then gave opportunity to Malays, to participating in the electricity industry. Up to the early 1940s, Malay participation was limited due to the staff hiring policies of the British, which prioritised expatriates. This article aims to study the human resources management and growth of Malay engineers in the electricity supply services in Peninsular Malaysia from 1949 to 1990. The following discussion uses archival and library research, analysing various primary and secondary sources such as the Colonial Office files, the Annual Reports of the Central Electricity Board (1949-1964), Annual Report National Electricity Board (1965-1990), ministry files, books, and articles. The findings show that the functions and roles played by Malay engineers in electricity supply services grew throughout the 1960s with their success in executive roles, including an increase in the number of those appointed as senior engineers to oversee administrative affairs and development projects.